Effect of pre-sowing treatments on seed germination and postgerminative seedling growth of acacia angustissima (mill.) - Ambebe, Titus Fondo; Awazi, Nyong Princely (Journal of Forests, 2024)
Seeds of Acacia angustissima were subjected to a control and five pre-sowing (soaking in cold water for 24 hours, soaking in hot water (100° C) for 5 minutes, immersion in 60 % H2SO4 for 30 seconds, immersion in 60 % H2SO4 for 5 minutes, and immersion in 60 % H2SO4 for 15 minutes) treatments. The number of seeds that sprouted was recorded daily for calculation of germination indices. When there had been no further germination in any of the treatments for four weeks, the height, number of leaves, number of leaflets, and root length of seedlings were determined. One-way analysis of variance was used to test the effects of the pre-sowing treatments on seed germination and seedling growth. Final Germination Percentage, Germination Rate Index, and Seedling Vigour Index were significantly higher in the warm water than other five treatments which displayed similar responses of the traits. Similar, the warm water pre-treatment resulted in the longest seedlings, when shoot height and / or root length was considered. There was no significant effect of treatment on Mean Germination Time, number of leaves, and number of leaflets. The findings suggest that hot water pre-sowing treatment is the most suitable for seed germination and initial seedling height attainment of Acacia angustissima.